Experimental Air Warming of a Stylosanthes capitata, Vogel Dominated Tropical Pasture Affects Soil Respiration and Nitrogen Dynamics - Gonzalez-Meler, Miquel A.; Silva, Lais B. C.; Dias-De-Oliveira, Eduardo; Flower, Charles E.; Martinez, Carlos A. (Frontiers in Plant Science, 2017)
Warming due to global climate change is predicted to reach 2°C in tropical latitudes. There is an alarming paucity of information regarding the effects of air temperature on tropical agroecosystems, including foraging pastures. Here, we investigated the effects of a 2°C increase in air temperature over ambient for 30 days on an established tropical pasture (Ribeirão Preto, São Paulo, Brazil) dominated by the legume Stylosanthes capitata Vogel, using a T-FACE (temperature free-air controlled enhancement) system. We tested the effects of air warming on soil properties [carbon (C), nitrogen (N), and their stable isotopic levels (δ13C and δ15N), as well as soil respiration and soil enzymatic activity] and aboveground characteristics (foliar C, N, δ13C, δ15N, leaf area index, and aboveground biomass) under field conditions. Results show that experimental air warming moderately increased soil respiration rates compared to ambient temperature. Soil respiration was positively correlated with soil temperature and moisture during mid-day (when soil respiration was at its highest) but not at dusk. Foliar δ13C were not different between control and elevated temperature treatments, indicating that plants grown in warmed plots did not show the obvious signs of water stress often seen in warming experiments. The 15N isotopic composition of leaves from plants grown at elevated temperature was lower than in ambient plants, suggesting perhaps a higher proportion of N-fixation contributing to tissue N in warmed plants when compared to ambient ones. Soil microbial enzymatic activity decreased in response to the air warming treatment, suggesting a slower decomposition of organic matter under elevated air temperature conditions. Decreased soil enzyme capacity and increases in soil respiration and plant biomass in plots exposed to high temperature suggest that increased root activity may have caused the increase seen in soil respiration in this tropical pasture. This response along with rapid changes in soil and plant 15N may differ from what has been shown in temperate grasslands.